Effect of 12 weeks of HIIT and Q10 supplementation on soleus muscle mitochondrial biogenesis in high-fat diet-induced obese rats - Masoud Rafati; Jabbar Bashiri; Roghayeh Poozesh Jadidi; Hassan Pourrazi (Shahid Beheshti University, 2022)
Purpose: little is known about the concomitant effects of HIIT and Q10 supplementation in modification of the mitochondorial biogenesis and function in obesity conditions. The aim of this study was to investigate the concomitant effects of HIIT and Q10 supplementation on soleus muscle mitochondorial content as well as NRF2, SIRT-1 and Tfam levels in obese male rarts.Methods: 48 rats randomized into six groups of lean, obese reference, obese control, obese+HIIT, obese+Q10 and obese concomitant (HIIT+Q10). Obesity was induced by high fat diet and HIIT) were done for 12 weeks (five sessions/week, with 10 intrval bouts for four min at 85-90% of v VO2 peak each session), while Q10 was consumed 500 mg/kg.bw daily. Data were measuered using western blot and Mitotrackervmethods and were analyzed by one-way ANOVA.Results: Mitochondorial content (P = 0.049) as well as NRF2 (P = 0.002), SIRT-1 (P = 0.007) and Tfam (P = 0.040) levels were significantly lower in obese control than lean group. Mitochondorial content and SIRT-1 levels of three intervention groups of obese+HIIT (P = 0.001), obese+Q10 (P = 0.001) and obese concomitant (P = 0.001) were significantly higher than obese control group and even could precede lean group values (with exception for mitochondorial content in obese+Q10 group (P = 0.001)). Moreover, only in both groups of obese+HIIT ( P= 0.033), and obese concomitant (P = 0.038), NRF2 levels were significantly higher compared to obese control group. However, in none of the intervention groups the Tfam levels had significant differences compared to obese control group (P > 0.05 in all three cases).Conclusions: Obesity likely suppresses soleus muscle mitochondorial biogenesis, or at least increases the removal rate of pre-existing mitochondria. However, HIIT as well as Q10 supplementation seems to partially capable to restore this down regulation, with a greater effects expected for HIIT. However, more investigations remain to be done due to lack of similar evidence and study limitations.